HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BARA-BARAYA MAKASSAR - Nurasni Vita Sari; Muldaniyah, Kartika Asli (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
During pregnancy, mothers must prepare themselves to welcome the birth of their baby. A healthy mother can give birth to a healthy and physically perfect baby with sufficient body weight. Maternal nutritional status in pregnancy affects the nutritional status of the fetus. Maternal food intake can enter the fetus through the umbilical cord that is connected to the mother's body. The purpose of this study was to determine the relationship between nutritional status and the incidence of anemia in pregnant women in the working area of the Baraya Baraya Health Center Makassar. The research design is quantitative. The researcher used a design with a cross sectional method, the number of samples was 45 respondents who met the inclusion criteria with purposive sampling technique. Data analysis was carried out by univariate, bivariate, with "Chi square test". The results of the study found that the p value was 0.000, meaning the p value (p < 0.005), then HA was accepted and Ho was rejected. From this study, there is a relationship between nutritional status and the incidence of anemia in pregnant women in the working area of the Baraya Health Center Makassar. Therefore, it is recommended that mothers continue to consume nutritious foods